Decarboxylative Negishi Coupling of Redox‐Active Aliphatic Esters by Cobalt Catalysis. Issue 40 (4th September 2018) - Liu, Xu‐Ge; Zhou, Chu‐Jun; Lin, E.; Han, Xiang‐Lei; Zhang, Shang‐Shi; Li, Qingjiang; Wang, Honggen
Abstract: A cobalt‐catalyzed decarboxylative Negishi coupling reaction of redox‐active aliphatic esters with organozinc reagents was developed. The method enabled efficient alkyl–aryl, alkyl–alkenyl, and alkyl–alkynyl coupling reactions under mild reaction conditions with no external ligand or additive needed. The success of an in situ activation protocol and the facile synthesis of the drug molecule (±)‐preclamol highlight the synthetic potential of this method. Mechanistic studies indicated that a radical mechanism is involved. Abstract : Keen to couple : A cobalt‐catalyzed decarboxylative Negishi coupling reaction of N ‐hydroxyphthalimide (NHPI) esters with organozinc reagents enabled efficient alkyl–aryl, alkyl–alkenyl, and alkyl–alkynyl coupling under mild conditions without an external ligand or additive (see scheme). The success of an in situ activation protocol and the facile synthesis of the drug molecule (±)‐preclamol highlight the potential of this method.